2022
DOI: 10.1017/s0962492922000034
|View full text |Cite
|
Sign up to set email alerts
|

Schwarz methods by domain truncation

Abstract: Schwarz methods use a decomposition of the computational domain into subdomains and need to impose boundary conditions on the subdomain boundaries. In domain truncation one restricts the unbounded domain to a bounded computational domain and must also put boundary conditions on the computational domain boundaries. In both fields there are vast bodies of literature and research is very active and ongoing. It turns out to be fruitful to think of the domain decomposition in Schwarz methods as a truncation of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 136 publications
0
8
0
Order By: Relevance
“…Without lack of generality, from now on suppose is calculate from the errors at the interface Γ. General methods to study the convergence of Schwarz algorithms can be found in [5,6,7].…”
Section: Convergence For Problems On An Infinite Time Windowmentioning
confidence: 99%
“…Without lack of generality, from now on suppose is calculate from the errors at the interface Γ. General methods to study the convergence of Schwarz algorithms can be found in [5,6,7].…”
Section: Convergence For Problems On An Infinite Time Windowmentioning
confidence: 99%
“…The solution process of problems on unbounded domains usually requires a domain truncation and, hence, artificial boundary conditions, leading to techniques such as perfectly matched layers (PML) or absorbing boundary conditions (ABC); see [3,5]. At the discrete level, these closely relate to the problem of approximating the Schur complement in some sense, which inspired a number of iterative solvers; see, e.g., [14,15] and the references therein. Our approach builds upon the eigendecomposition of the Schur complement, which for our model problem is very closely linked with the Fourier analysis of the Schur complement or, equivalently, the frequency domain analysis.…”
mentioning
confidence: 99%
“…Domain truncation is also important in domain decomposition where a given computational domain is decomposed into many smaller subdomains and then subdomain solutions are computed independently in parallel; see [15]. The solutions on the smaller subdomains can naturally be interpreted as solutions on truncated domains and, thus, it is of interest to use ABC or PML techniques at the interfaces between the subdomains; see also [9,10,14].…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Because the Helmholtz equation is at the heart of linear wave propagation, much effort has gone into both studying the properties of its solutions (for example, their asymptotic behavior as k \rightar \infty ) and designing methods for computing the solutions efficiently; for the latter, see, e.g., the recent review articles [18,32,48,49].…”
mentioning
confidence: 99%